Fractional SDEs with stochastic forcing: Existence, uniqueness, and approximation - Kubilius, Kęstutis (Nonlinear Analysis: Modelling and Control, 2023)
In this article, we are interested in fractional stochastic differential equations (FSDEs) with stochastic forcing, i.e., to FSDE we add a stochastic forcing term. The conditions for the existence and uniqueness of solutions of such equations are obtained, and the convergence rate of the implicit Euler approximation scheme for them is established. Such types of equations can be applied to the consideration of FSDEs with a permeable wall.